Overexpression of SFPQ Improves Cognition and Memory in AD Mice - Jinshan Tie; Hongxiang Wu; Wei Liu; Yuying Li; Lu Li; Suju Zhao; Zhijiao Yuan; Khan Mahmood; Shaochun Chen; Huidong Wu (Neural Plasticity)
Alzheimer’s disease (AD) is a complex neurodegenerative disorder with multifaceted pathogenesis, which has been extensively investigated, yet effective treatments remain lacking. Splicing factor proline and glutamine rich (SFPQ) is known to play a crucial role in neurodegenerative diseases, including antioxidant-related functions and regulating gene expression within brain neurons. However, the specific role of SFPQ in AD pathology is not well understood. In this study, an AD mouse model was established through lateral ventricular injection of amyloid-beta1–42 (Aβ1–42). Subsequently, adeno-associated virus was administered to overexpress SFPQ in the hippocampus of AD mice. The results demonstrate that SFPQ overexpression improves recognition and memory in AD mice, while reducing AD-related marker proteins such as amyloid precursor protein (APP) and Tau. Additionally, synaptic and memory-associated proteins, as well as antioxidant proteins like glutathione S-transferase (GST) and heme oxygenase-1 (HO-1), were upregulated. The ratio of antiapoptotic protein Bcl-2 to proapoptotic protein Bax also increased. Furthermore, phosphorylated phosphoinositide 3-kinase (p-PI3K)/PI3K and phosphorylated protein kinase B (p-AKT)/AKT ratios were elevated, indicating activation of the PI3K/AKT signaling pathway. These findings suggest that SFPQ may serve as a promising molecular target for the prevention and treatment of AD.